THE ROLE OF HOSPITAL AND CLINICAL PHARMACISTS IN ANGOLA AND BRAZIL: AN INTERCULTURAL EXPERIENCE REPORT - Vaneza Inês Baza Zau; Maria Carmélia Almeida Neta; Fagner Carvalho Leite; Erica Carneiro Ricarte; Francisco Clébison Chaves Lopes; Alane Rolim Moreira; Odilon Rodrigues Sarmento Neto; João da Costa André (Artefactum - revista de estudos interdisciplinares, 2026)
This experience report analyzes the role of hospital and clinical pharmacists in Angola and Brazil, based on the trajectory of an Angolan author with previous experience in Angolan health institutions and current experience in a Brazilian public hospital. The study adopts a qualitative, descriptive, and exploratory approach, grounded in direct observation, field notes, and comparative analysis of professional practices. The findings show that, in Brazil, clinical pharmacy has a stronger presence within multidisciplinary teams and greater pharmacist participation in patient care. In Angola, structural limitations, shortage of resources, and a lower level of consolidation of clinical practice were observed, although local initiatives of professional commitment and resilience were also identified. It is concluded that strengthening pharmaceutical care depends on professional training, institutional support, professional recognition, and the adaptation of clinical practices to local realities.